Effective sequestration of levofloxacin from wastewater by biochar-supported manganese dioxide composite: experimental study and modelling analyses - Adeyi, Abel Adekanmi; Bitrus, Nathan Kura; Abdullah, Luqman Chuah; Popoola, Lekan Taofeek; Chijioke-Okere, Maureen; Omotara, Oluwagbenga Olawale; M.Saber, Shihab Ezzuldin (Korean Society of Environmental Engineering, 2022)
Manganese dioxide was laden hooked on biochar sourced from chicken feather to obtain a biochar-supported manganese dioxide (BSM) composite. In order to reduce the costs of acquisition and minimise the disposal of adsorbents, prepared BSM composite were employed in the sequestration of Levofloxacin (LEVO) from aqueous environment. The physico-chemical features and the adsorption mechanisms of prepared BSM, prior and after the adsorption of LEVO molecules were revealed by Scanning Electron Microscopy and Fourier Transform Infrared spectroscopy techniques. The influence of adsorption parameters including BSM dose, initial concentration, temperature and residence time were studied. The removal of LEVO was significantly influenced by all parameters. Equilibrium data has its fitness in the following order: Redlich-Peterson ˃ Langmuir ˃ Freundlich models. The maximum adsorption capacity of BSM for LEVO was 104.13 mg/g. The kinetic analysis indicates best fittings for pseudo-second-order model suggesting chemisorption as controlled mechanism. Besides, liquid film and intra-particle diffusion had a vital influence on the LEVO sequestration process. Exothermic and spontaneous nature of LEVO uptake by BSM was revealed by thermodynamic analysis. The findings suggested that prepared BSM show high sorption capacity, and recyclability potential towards separation of LEVO from contaminated pharmaceutical wastewater.